Damping effects of linear and nonlinear tuned mass dampers on nonlinear hinged-hinged beam. (15th September 2018) - Wang, Y.R.; Feng, C.K.; Chen, S.Y.
Abstract: This study analyzes the vibration reduction of a tuned mass damper (TMD) applied to a hinged-hinged nonlinear Euler-Bernoulli beam. We compare the effects of linear and nonlinear tuned mass dampers (LTMD/NLTMD) and obtain results undiscovered in previous studies. We analyze the frequency responses (fixed points) of the system using the method of multiple scales (MOMS) and obtain analytical solutions for the NLTMD in the frequency and time domains using Dimensional Analysis and the Perturbation Method. The present study shows that when the damping coefficient ( λ ), TMD mass ( m D ), TMD initial displacement ( A ) and nonlinear spring constant ( β ) of the NLTMD fulfill a function relationship λ = 3 m D β A, the damping and nonlinear elastic effects cancel each other out, and the nonlinear damping frequency coincides with the linear natural frequency. With a fixed damping coefficient and an LTMD or NLTMD at a fixed position, optimal damping is achieved when the product of the TMD mass and spring constant are at fixed values. Finally, we use the Floquet transition matrix of the system and Floquet multipliers (F.M.) to create the basin of attraction (BOA) and analyze the stability of the system under aerodynamic forces. Highlights: The analytical solution for the nonlinear tuned mass damper (NLTMD) was obtained. When the damping coefficient and nonlinear spring constant of the NLTMD fulfill a function relationship, the nonlinear damping frequency coincides with the linear natural frequency. With a fixed damping coefficient and a linear tuned mass damper (LTMD) or NLTMD at a fixed position, optimal damping is achieved when the product of the TMD's mass and spring constant are at fixed values.